Foraging behavior of the sea urchin Mesocentrotus nudus exposed to conspecific alarm cues in various conditions - Xiaomei Chi (Nature Portfolio, 2021)
Abstract Conspecific alarm cues crushed from Mesocentrotus nudus prevent sea urchins from foraging the kelp, but do not repel them far away from the kelp. However, it remains largely unknown of whether this phenomenon was affected by conspecific alarm cues or by the attraction of the kelp. The present study found no significant difference in the duration in the danger area with or without the kelp around conspecific alarm cues. This suggests that the phenomenon is the strategy of sea urchins but not by the attraction of kelp. We found that conspecific alarm cues appearing between the kelp and sea urchins significantly affected foraging behavior of sea urchins fasted for 21 days. This indicates that conspecific alarm cues can effectively prevent fasted sea urchins from foraging the kelp. Further, there was no correlation between foraging velocity and the duration in the danger area. Pearson correlation analysis revealed no significant correlation between foraging velocity and the duration in the safety area close to different amounts of conspecific alarm cues, suggesting that conspecific alarm cues prevent sea urchins with strong foraging ability to forage. Collectively, the present results indicate that conspecific alarm cues as highly available biological barriers are cost-effective approaches to preventing overgrazing of sea urchins in the protection of kelp beds ecosystems. Notably, the present study is a short-term laboratory investigation that does not consider the complexity of natural conditions. Future studies are essential to test the present findings in the field.